Preliminary detection of marine debris pollution in mangrove ecosystem on Moti Island as a conservation area in North Maluku, Indonesia - Halikuddin Umasangaji; Yunita Ramili; Anisa Eka Putri Hatari (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Mangrove ecosystem have been recognized as a paramount area in terms of marine debris traps despite of their essential role in carbon sequestration and coastal protected. This study collected marine debris and observed mangrove conditions on Moti Island as one of the conservation area in North Moluccas. The results of this study showed that R. apiculata had the highest species composition at both stations. The mangrove density at Station 2 (622 ind.h-1) which was higher than Station 1 (589 ind.h-1). The total number of marine debris was 214 items, with the highest composition of plastic debris (96% - 97%) and the lowest was metals. Most of the marine debris was classified as macro debris. The total weight of marine debris was higher at Station 2 (1812.79 g) than at Station 1 (1727.69 g) Furthermore, the density and accumulation values of marine debris at Station 2 were higher (0.12 items.m-2 and 6.043 g.m-2) than those at Station 1 (0.063 items.m-2 and 2.879 g.m-2). The mangrove beach cleanliness index at both research stations was categorized as very clean (Station 1) and clean (Station 2). The relationship between marine debris and mangrove density showed a positive correlation despite low correlation with an r2 value of 0.24. Meanwhile, according to single way ANOVA, there was no significant difference in marine debris abundance between the two stations. Polymer identification through commercial labels implied the dominance of PET, LDPE and PP types at both stations.Keywords:Marine debrisMangrove ecosystemConservation areaMoti islandNorth Moluccas